Radon transforms, geometry, and wavelets : AMS Special Session, January 7-8, 2007, New Orleans, Louisiana : Workshop, January 4-5, 2007, Baton Rouge, Louisiana - Ólafsson, Gestur (Contemporary mathematics (American Mathematical Society) ;, 2008)
"This volume is based on two special sessions held at the AMS Annual Meeting in New Orleans in January 2007, and a satellite workshop held in Baton Rouge on January 4-5, 2007. It consists of invited expositions that together represent a broad spectrum of fields, stressing surprising interactions and connections between areas that are normally thought of as disparate. The main topics are geometry and integral transforms."--Jacket.